2014
DOI: 10.1111/bjd.12994
|View full text |Cite
|
Sign up to set email alerts
|

Actinic damage on the back is significantly determined by MC1R variants and previous sun exposure compared with other body sites in a multivariate analysis

Abstract: The particular effect of MC1R variants and sun exposure during recreational time on dorsal actinic damage indicates that actinic damage on the back is more informative regarding susceptibility to sunlight and past sun exposure associated with melanoma risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 31 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…All 1668 histologically confirmed patients with melanoma who were recruited from 2008 to 2015 as part of the M3 case–control study were included . The participants originated mainly from Vienna, the province of Lower Austria, and Burgenland (Table S1; see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 1668 histologically confirmed patients with melanoma who were recruited from 2008 to 2015 as part of the M3 case–control study were included . The participants originated mainly from Vienna, the province of Lower Austria, and Burgenland (Table S1; see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing data were available for CDKN2A from 474 participants, for exon 2 of CDK4 from 109 patients and for MC1R from 875 participants, as described previously . Additionally, 93 new cases were sequenced for CDKN2A , 123 for CDK4 and MITF , and 89 for MC1R .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More detailed information about the study population has been reported previously. 11 Written consent was obtained from all participants. This study was approved by the ethics committee of the MUV.…”
Section: Study Populationmentioning
confidence: 99%
“…): Wrinkling on the face was defined as deep skin lines occurring on the forehead, periorbital, and perioral region, whereas wrinkling on the neck was defined as deep skin lines, commonly appearing in a characteristic rhomboid pattern. 11 Freckling was defined as persistent areas of hyperpigmentation, resulting in a mottled, irregular skin appearance; 12,13 and solar lentigines were defined as brown, macular lesions with sharp margins. Dependent on their severity, these signs of actinic skin damage were graded, as described elsewhere, 14 as absent, mild, moderate, or severe.…”
Section: Assessment Of Sunburn History and Signs Of Actinic Skin Damagementioning
confidence: 99%